First Encounters: Effects of the Microbiota on Neonatal Brain Development - Gars, Aviva; Ronczkowski, Nicole M.; Chassaing, Benoit; Castillo-Ruiz, Alexandra; Forger, Nancy G. (Frontiers in Cellular Neuroscience, 2021)
The microbiota plays important roles in host metabolism and immunity, and its disruption affects adult brain physiology and behavior. Although such findings have been attributed to altered neurodevelopment, few studies have actually examined microbiota effects on the developing brain. This review focuses on developmental effects of the earliest exposure to microbes. At birth, the mammalian fetus enters a world teeming with microbes which colonize all body sites in contact with the environment. Bacteria reach the gut within a few hours of birth and cause a measurable response in the intestinal epithelium. In adults, the gut microbiota signals to the brain via the vagus nerve, bacterial metabolites, hormones, and immune signaling, and work in perinatal rodents is beginning to elucidate which of these signaling pathways herald the very first encounter with gut microbes in the neonate. Neural effects of the microbiota during the first few days of life include changes in neuronal cell death, microglia, and brain cytokine levels. In addition to these effects of direct exposure of the newborn to microbes, accumulating evidence points to a role for the maternal microbiota in affecting brain development via bacterial molecules and metabolites while the offspring is still in utero. Hence, perturbations to microbial exposure perinatally, such through C-section delivery or antibiotic treatment, alter microbiota colonization and may have long-term neural consequences. The perinatal period is critical for brain development and a close look at microbiota effects during this time promises to reveal the earliest, most primary effects of the microbiota on neurodevelopment.